The Role of C – Reactive Proteins as Indicator of Antibiotic Therapy among Patients with Acute Exacerbation of Chronic Obstructed Pulmonary Disease (Medical Forum Monthly, 2021)
Objective: This study was conducted to define role of CRP as indicator of antibiotic therapy among patients with COPD.Study Design: Descriptive case series StudyPlace and Duration of Study: This study was conducted at the Department of Pulmonology, Shalamar Medical and Dental College Lahore, Akhtar Saeed Medical College Lahore and Tehsil Head Quarter Hospital, Shakargarh from June, 2019 to January, 2020.Materials and Methods: The study included 100 cases fulfilling inclusion criteria. Serum CRP levels were measured in all patients and were categorized as: low CRP (<40 mg/L) and high CRP (>40 mg/L). Patients in both groups received antibiotic therapy (Levofloxacin 500mg twice daily per oral) for 7 days. Patients were assessed for clinical success (absence of dyspnea and sputum).Results: High CRP level was observed in 65(65%) patients and low in 35(35%) patients. Clinical success was achieved among 14(40%) patients in low CRP group and 56(86.2%) patients with high CRP group (p<0.05).Conclusion: Majority of patients had high CRP level (>40mg/L). So, CRP level can be used as an indicator for commencement of antibiotic therapy among patients with acute exacerbation of COPD.